Islam Nusantara: The Conceptual Vocabulary of Indonesian Diversity - Saskia Schaefer (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2021)
This article focuses on the concept “Islam Nusantara” in debates about Islam in Southeast Asia, particularly in Indonesia. Descriptive and prescriptive, the term is a call for acknowledging and accepting the diversity of Islamic practice and belief in Indonesia. I make three arguments. First, while the concept and term “Islam Nusantara” is new in its current variant – closely tied to a particular group of thinkers within the NU – most of what the term describes is neither new nor as locally specific to Southeast Asia as the term suggests. The term encapsulates a thousand-year-old practice of plurality and ideals of pluralism that has been historically more typical for Islamicate societies than modern readings often acknowledge. Second, while it describes a lived reality, “Islam Nusantara” has also become a normative call for renewed pride in and support for diversity of practice and belief. It is a call issued in a deeply competitive landscape in which a variety of actors link religion to politics in new and intense ways, but at the same time “Islam Nusantara” continues to contain some remnants of the foundational vision of the Nahdlatul Ulama. One question that the proponents of the term need to work out is its normative relationship to pluralism – itself a complicated and contested term. The third argument pertains to the normative ambitions of those promoting the concept. I argue that in order to fully expand and make good on its potential, the concept needs to reach beyond Java-centric notions of Islam.